Cross-modal perception : are there sensory processing differences between students of engineering and psychology? - Koh, Gladys Qi Shan (2017)
Cross-modal correspondences refer to the non-arbitrary associations between seemingly unrelated information from different sensory modalities. For example, people usually associate a loud sound to something big in size, and most people look higher up in space when they hear a high-pitched sound around them. In the linguistic domain of cross-modal correspondences (i.e. sound symbolism), certain auditory features of speech are associated with particular visual attributes of objects such as shape and size. Specifically, there is a consistent tendency for people to match ‘bouba’ to rounded shapes and ‘kiki’ to jagged shapes – this is known as the Bouba-Kiki effect. Individuals with Autism Spectrum Disorder (ASD) have been shown to display less cross-modal congruency, theorised to be due to sensory integration deficits. The present study looks at the possible links in a different population known to share autism-related traits with individuals with ASD: Engineers. In an online study, Engineering/Computer Science and Psychology undergraduates completed the Alien Zoo game (a measure of an individual’s propensity for sound symbolic mapping) and the Adolescent/Adult Sensory Profile (an established tool assessing for sensory integration deficits). As predicted, Engineering/Computer Science undergraduates gave less congruent responses on the Alien Zoo game. However, scores on the Alien Zoo game were not related to scores on the Adolescent/Adult Sensory Profile. Hence, there was insufficient evidence to conclude that Engineering/Computer Science undergraduates display atypical sensory integration. In addition, the use of terminology in the literature and the appropriateness of the Adolescent/Adult Sensory Profile used in the Singapore context were discussed.